(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to investigate the nature of the relationship between positive classroom environment and both students’ mental health and academic achievement in light of theoretical literature and empirical studies published from 2015 to 2025، The significance of this research stems from the growing global interest in students’ mental health and the impact of the school environment on their overall well-being and academic performance, particularly following the COVID-19 pandemic، The study seeks to identify the core components of a positive classroom environment, analyze the relationship between these components and mental health and academic achievement, and explore the mediating and moderating factors of these relationships، The research employed a Thematic Analysis approach to review and analyze studies published in internationally recognized academic databases، The research population comprised 66 studies focusing on students from elementary through secondary educational stages, with rigorous inclusion and exclusion criteria applied to ensure scientific quality، Data were analyzed through six sequential phases of thematic analysis, including initial coding, searching for themes, reviewing themes, and defining them، The findings revealed a consistent positive relationship between positive classroom environment and both mental health and academic achievement, with significant mediating variables such as motivation and self-efficacy، The research recommends adopting a comprehensive approach to improving the school environment, training teachers to build supportive classroom environments, and conducting further longitudinal experimental studies in Arab contexts.